Adolescent and young adult cancers in India–Findings from the National Cancer Registry Programme. (June 2022) - Mathur, Prashant; Nath, Anita; K, Sathish Kumar
Abstract: Background: The adolescent and young adult (AYA) age group is a bridge between pediatric and adult age groups. The present study describes the epidemiology of cancers in the AYA age group in India. Methods: The data of primary site cancers in the age group of 15–39 years from the 28 Population Based Cancer Registries (PBCRs') and 58 Hospital Based Cancer Registries under the National Cancer Registry Programme for the reporting year 2012–2016 was analysed. Results: The median age adjusted incidence rate (AAR) was 22.2 per 100, 000 among males and 29.2 per 100, 000 among females. The age-specific incidence rate increased with increasing age in both genders with the highest recorded numbers in the 35–39 age group. The proportion of myeloid leukaemia and non-Hodgkin's lymphoma was highest in the 15–24 age group. Cancers of the breast, thyroid, mouth and tongue constituted the leading sites between 30 and 39 years. There was a significant increase in the incidence among AYA males (APC=0.9) between 1985 and 2015, while a decline in incidence was observed for females, which was not significant (APC=−0.2). The majority of patients had locoregional spread of cancer at the time of diagnosis. The projected number of cancer cases in both genders are expected to increase to 178, 617 in 2025. Conclusion: Cancers in the AYA population are a concern in India. Since AYA oncology appears to be evolving in India, a robust health care system and suitable AYA cancer care policies and programmes are strongly needed to improve disease outcomes and survival. Highlights: The Age Adjusted Incidence Rate for AYA cancers (15–39 years) was found to be higher in females than males. Breast, thyroid, mouth and tongue cancers were the leading sites between 30 and 39 years The there has been a significant rise in breast cancer and decline in cervical cancer incidence over more than two decades. Majority of the AYA cancer patients had a locoregional disease spread at the time of diagnosis. Projected number of AYA cancer cases are expected to increase to 178, 617 in 2025.